Pemanfaatan Koleksi BI Corner Perpustakaan Universitas Muhammadiyah Sumatera Utara sebagai Bahan Rujukan Penelitian bagi Mahasiswa - Amalia Safitri,; Yasmin, Nabila (Literatify : Trends in Library Developments, 2024)
UMSU Library has several corner services including BI Corner, Muhammadiyah Corner, Japan Corner, French Corner, and Indian Corner. The purpose of this research is to find out how the utilization of the BI Corner collection as research reference material by students and what are the obstacles faced by students. The method used in this research is qualitative method. The data collection technique is by making direct observations to the BI Corner service in the UMSU library. In addition, the author also conducted an interview with a librarian who knew the BI Corner service and also conducted interviews with 3 users who visited the BI Corner service, as well as conducting documentation activities on several activities that the author went through to make research. The results of this study show that students have utilized the BI Corner collection for their research reference material and the obstacles faced by the library users are that the library users still have difficulty finding BI Corner collections and the collections owned by BI Corner are not fully complete.